Research on modeling and simulation of arc characteristics with very large length–diameter ratio - Lihua Zhao; Yulu Yang; Xiaolong Huang; Qiang Zhang; Shuangwei Zhao; Chenxi Yang; Shenli Jia (AIP Advances)
The vacuum circuit breaker has become a research hotspot in the field of high voltage electrical appliances because of its advantages of no pollution and long life. At the moment of arc breaking, the distribution of current density is not uniform. The arc will briefly deviate and shrink. If the axial magnetic field design is insufficient, it will continue to stay in this state. At this time, the anode spot releases and provides a large number of particles to the plasma region, aggravates the arc combustion, and makes the arc form shrink and concentrate, which is not conducive to fracture. In this paper, a three-dimensional magnetohydrodynamic model considering arc deflection and contraction is established. By measuring the offset magnetic field and comparing it with the simulation, the characteristics of the plasma magnetic field and arc plasma under different bias contraction states are given, and the distribution of anode energy flux density under the influence of the offset magnetic field is given. It is found that the offset magnetic field in the axial magnetic contact and the offset arc form a positive feedback. Thus, the arc is forced outward as a whole. The energy flux density of the anode near the edge of the contact is higher, which causes the arc to burn outward and is not conducive to the arc breaking. The research results are helpful in improving the breaking performance of vacuum circuit breakers and provide a theoretical basis for the development of vacuum breaking theory.